THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, LIQUIDITY, AND COMPANY SIZE ON THE VALUE OF COMPANIES IN THE ENERGY SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE OVER THE 2021–2023 PERIOD - Muhammad Mustaqim Sutjiptadi; Mardi; Dwi Kismayanti Respati (Research Trend in Technology and Management, 2025)
For the 2021–2023 timeframe, this study looks at how firm worth is affected by corporate social responsibility (CSR), profitability (NPM), liquidity (CR), and company size (Ln total assets) the Indonesia Stock Exchange (IDX) lists businesses in the energy industry. For the quantitative data used in this study, annual reports and corporate sustainability reports were employed as secondary data sources. Thirty-four businesses in total met the sample requirements using purposive sampling, which produced 102 observational data sets. The analysis technique utilized with IBMM SPSS 26 software is multiple linear regression analysis. According to findings from the research, net profit margin significantly increases firm value while corporate social responsibility significantly decreases it, whereas current ratio and firm size have no discernible effects. The value of the business is simultaneously greatly effected by the four factors. These findings suggest that while non-strategic CSR disclosure, company size, and liquidity are insufficient to affect investor perceptions of company value, financial performance particularly profitability plays a significant role in raising company value.